Primnoidae (Cnidaria: Octocorallia: Calcaxonia) of the Okeanos Explorer expeditions (CAPSTONE) to the central Pacific - Cairns, Stephen D. (Zootaxa, 2018)
This paper discusses and illustrates the 23 primnoid species collected by the R/V Okeanos Explorer in the US marine protected areas in the central and western Pacific, ranging from the Musician Seamounts in the north to American Samoa to the south, and the northern Mariana Islands to the west (CAPSTONE expeditions, 2015-2017). In situ photographs are provided for most species. Thirteen of the 23 species are described as new, as well as two new genera. One new genus, Macroprimnoa, possesses some of the largest polyps in the family. A dichotomous key is provided to facilitate comparisons among the 27 species of Calyptrophora. An update of the abyssal octocorallian species occurring deeper than 3000 m is provided, increasing that number from 39 to 49 species. The character of the articulating ridge, found on the distal edge of the basal body wall scales, is re-evaluated, resulting in four genera having this character state, and requiring the description of the new genus Pseudonarella.